Influência do grupo de pares e uso de drogas ilícitas entre adolescentes brasileiros: um estudo transversal - Kelly Oliva Jorge (2018)
The aim of the present cross-sectional study was to examine illicit drug use and associations with socioeconomic factors as well as peer group influence among Brazilian adolescents aged 15 to 19 years. Two-stage cluster sampling was adopted, involving the random selection of public and private schools from the nine administrative districts of a Brazilian state capital and the random selection of classrooms at each school. Illicit drug use was the outcome and was measured through the question: “Have you ever used any illicit drugs (marijuana, inhalants, hypnotics, cocaine/crack, hallucinogens, amphetamines and opioids) in your life?”. The most important group of friends was ranked as school, family, religious activities and sports/culture. The area-based Health Vulnerability Index (HVI) was used to assess socioeconomic status. Data from 891 adolescents were analyzed using the chi-squared test and logistic regression. The overall rate of illicit drug use was 15.2%. Gender heterogeneity within groups (OR = 3.14; 95%CI: 1.63-6.06), religion-based friendships (OR = 0.36; 95%CI: 0.17-0.75) and sports/culture-based friendships (OR = 0.44; 95%CI: 0.22-0.87) remained significantly associated with illicit drug use. Adolescents who lived in less vulnerable areas had higher chance of drug use in comparison with those living in more vulnerable areas. Religion-based and sports/culture-based friendships seem to demonstrate a protective effect against lifetime illicit drug use. Gender heterogeneity within groups and residing in a less vulnerable area increased the chances of adolescents reporting illicit drug use.